Strategic planning for the development of Ukrainian agriculture in the face of climate change - Ostapenko Anna (Comparative Economic Research. Central and Eastern Europe, 2016)
The essence of the "strategic planning" is explored and the peculiarities of strategic planning in the agricultural sector are defined. Global climate change as a factor stimulating the formation of new approaches to strategic planning of agricultural development is considered, and the impact of climate change on the agricultural sector of Ukraine is evaluated. A predictive model of changes in the parameters of agricultural production under expected climate change conditions is constructed, and organizational, socio-economical and environmental components of the strategy of agricultural development are outlined and the conceptual bases for improvement of strategic planning for the development of the agricultural sector in the face of climate change are substantiated.
Keywords: 330; strategic planning; agriculture; climate change; predictive model; Ukraine